Public management : organizations, governance, and performance - O'Toole, Laurence J., 1948-; Meier, Kenneth J., 1950- (Cambridge, U. K. : Cambridge University Press, 2011)
'How effective are public managers as they seek to influence how public organizations deliver policy results? How, and how much, is management related to the performance of public programs? What aspects of management can be distinguished? Can their separable contributions to performance be estimated? The fate of public policies in today's world lies in the hands of public organizations, which in turn are often intertwined with others in latticed patterns of governance. Collectively, these organizations are expected to generate performance in terms of policy outputs and outcomes. In this book, two award-winning researchers investigate the effectiveness of management in the public sector. Firstly, they develop a systematic theory on how effective public managers are in shaping policy results. The rest of the book then tests this theory against a wide range of evidence, including a data set of 1,000 public organizations'--
Includes bibliographical references (p. 291-308) and index.
Keywords: Public management; Administrative agencies -- Management